PERKEMBANGAN ILMU ADMINISTRASI DAN MANAJEMEN - Basri, Muhammad (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Abstract: This research aims to investigate the development of administration and management science along with the evolution of people's lives in various aspects such as economic, social, political and others. The research method used is library research, which involves collecting data from various sources of library information such as research results, journals and reference books. The research results show that administration has become a very vital field in managing organizations and institutions, both in the public and private sectors. Educational administration and management is also important in improving the quality of education, with a deep understanding of the concepts, principles and practices of administration and management as the key to success. Complex factors such as changes in social, economic, political and technological structures influence the development of this science, which has an impact on the evolution of the field of administration and management. The contribution of this knowledge to organizational practice and community development is very significant, providing an important contribution in managing organizations and advancing society. A deep understanding of the concepts and principles of administration and management encourages the creation of more efficient, effective and adaptive management processes in the organizational context.